Directional bending wave propagation in periodically perforated plates. (20th January 2015) - Andreassen, Erik; Manktelow, Kevin; Ruzzene, Massimo
Abstract: We report on the investigation of wave propagation in a periodically perforated plate. A unit cell with double-C perforations is selected as a test article suitable to investigate two-dimensional dispersion characteristics, group velocities, and internal resonances. A numerical model, formulated using Mindlin plate elements, is developed to predict relevant wave characteristics such as dispersion, and group velocity variation as a function of frequency and direction of propagation. Experimental tests are conducted through a scanning laser vibrometer, which provides full wave field information. The analysis of time domain wave field images allows the assessment of plate dispersion, and the comparison with numerical predictions. The obtained results show the predictive ability of the considered numerical approach and illustrate how the considered plate configuration could be used as the basis for the design of phononic waveguides with directional and internal resonant characteristics.